Uncovering misconceptions of apparent deviations from Mendel's Laws in 12th grade biology textbooks in Pontianak - Annisafira Nanda Rosa; Wolly Candramila; Eko Sri Wahyuni (University of Muhammadiyah Malang, 2025)
Textbooks are essential learning resources for both teachers and students, but they often contain misconceptions that can affect students' understanding of key concepts, particularly in biology. Misconceptions can arise from inaccurate or incomplete information, and they may lead to incorrect conceptual understanding. The clarity and accuracy of concepts presented in textbooks are crucial to preventing misconceptions and ensuring that students grasp complex biological topics. This study aims to identify and describe the types of misconceptions found in four twelfth-grade biology textbooks on the topic of apparent deviations from Mendel's laws. The four books were selected as the most widely used textbooks based on a direct survey conducted with 27 12th-grade biology teachers in Pontianak City during the first semester of the 2021/2022 academic year. This study reveals that three of the four analyzed books (B, C, and D) contain misconceptions, while Book A presents accurate information. Ten potential misconceptions found include misidentification (5), oversimplification (2), and obsolete terms (2) and undergeneralization (1), particularly in the explanation of epistasis and polygenic inheritance. Accurate and clear presentation in textbooks is essential to reduce misconceptions and improve students' understanding of complex biological concepts, as shown by the accurate content in Book A.